The Attitude of Hungarian Authorities towards the Writers: Detailed Account of Cultural Life in Hungary in Years Following the Uprising - Héderváry, Claire de (1959)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations Information Office The role of the Hungarian intelligentsia during the uprising and the years thereafter.